Breast-Conserving Therapy Has Better Prognosis for Tumors in the Central and Nipple Portion of Breast Cancer Compared with Mastectomy: A SEER Data-Based Study - Wang, Jing; Wang, Xiaoyu; Zhong, Zhenyu; Li, Xue; Sun, Jiazheng; Li, Jie; Huang, Jiefeng; Li, Yunhai; Ren, Guosheng; Li, Hongzhong (Frontiers in Oncology, 2021)
Background and Objectives: Currently the location of primary tumor was an independent prognostic factor of breast cancer. Tumors in the central and nipple portion (TCNP) had poor prognosis than other peripheral quadrants. The breast-conserving therapy (BCT) is becoming increasingly common worldwide in the breast cancer operation. However, whether the availability of breast-conserving therapy (BCT) was performed for TCNP remained a matter of debate. We sought to investigate whether BCT was suitable for TCNP with respect to survival outcomes, compared with mastectomy therapy. Methods: Utilizing the Surveillance, Epidemiology, and End Results (SEER) database, we obtained TCNP breast cancer patients diagnosed during the period of 2010-2015. One-to-one (1:1) propensity score matching (PSM) was applied to construct a matched sample consisting of pairs of BCT and mastectomy groups. Univariate and multivariate Cox proportional hazard models were applied to estimate the factors associated with breast cancer-specific survival (BCSS) and overall survival (OS). And survival analysis was performed with the Kaplan-Meier method. Results: In the overall cohort, a total of 9900 patients were enrolled. We found patients with BCT showed significantly better BCSS (log-rank, P<0.001) and OS (log-rank, P<0.001) than mastectomy group before PSM. The same finding was also shown in 5820 patients after PSM. Additionally, none of the subgroups, including age, sex, race, histological grade, AJCC stage and molecular subtype undergoing mastectomy therapy had better BCSS superior to BCT. Conclusions: Our study was the first research to show that BCT exhibited superior prognosis in the cohort of TCNP from SEER databases than mastectomy therapy. This finding could provide a cue for the treatment strategies, when coming to suitable TCNP patients, especially those with strong willingness to conserve breast.